1993
DOI: 10.1021/jm00053a008
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based design of inhibitors of purine nucleoside phosphorylase. 1. 9-(Arylmethyl) derivatives of 9-deazaguanine

Abstract: Purine nucleoside phosphorylase (PNP, EC 2.4.2.1) is a salvage enzyme important to the T-cell-mediated part of the immune system and as such is an important therapeutic target. This paper describes the design, synthesis, and enzymatic evaluation of potent, competitive inhibitors of PNP. Potential inhibitors were designed using the three-dimensional structure of the enzyme in an iterative process that involved interactive computer graphics to model the native enzyme and complexes of it with the inhibitors, Mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(73 citation statements)
references
References 25 publications
5
68
0
Order By: Relevance
“…For some targets such as influenza virus neuraminidase (35), HIV protease (for a selected sample see Ref. 36), purine nucleoside phosphorylase (37), and thymidylate synthase (38), these approaches have led to the de novo design of compounds that show promising therapeutic benefit as well as being useful tools for probing the biological function of the proteins. Here we have successfully applied this approach to (i) gain further insight into the sites and mode of interaction of native peptide inhibitors of human sPLA 2 -IIA that were originally derived from the primary sequence of the enzyme itself (30) and (ii) improve the potency of specific inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…For some targets such as influenza virus neuraminidase (35), HIV protease (for a selected sample see Ref. 36), purine nucleoside phosphorylase (37), and thymidylate synthase (38), these approaches have led to the de novo design of compounds that show promising therapeutic benefit as well as being useful tools for probing the biological function of the proteins. Here we have successfully applied this approach to (i) gain further insight into the sites and mode of interaction of native peptide inhibitors of human sPLA 2 -IIA that were originally derived from the primary sequence of the enzyme itself (30) and (ii) improve the potency of specific inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Cocrystallization with various inhibitors, together with molecular modelling, were employed in attempts to develop more potent inhibitors [14][15][16]. These studies suggested that binding of guanine analogue inhibitors involves the purine ring N(7) as a hydrogen bond acceptor [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cocrystallization with various inhibitors, together with molecular modelling, were employed in attempts to develop more potent inhibitors [14][15][16]. These studies suggested that binding of guanine analogue inhibitors involves the purine ring N(7) as a hydrogen bond acceptor [15]. This is in striking contrast to our finding that a variety of N(7)-alkylguanosines, in which the ring N (7) is blocked and the imidazole ring carries a positive charge, are good substrates, some even superior to the parent guanosine [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…These suggest that the simultaneous occupation of both substrate-binding sites enables PRibPP to have high affinity to the enzyme. This bi-substrate mimicking approach is reported in the study to design purine-nucleoside phosphorylase (PNP) inhibitor for the treatments of psoriasis and cultaneous T-cell lymphoma, which is one of the most famous and successful studies using the structure-based drug design technique [24][25][26][27][28]. PNP catalyzes the reversible conversion of purine nucleosides, (deoxy)guanosine or (deoxy)inosine, to the base and sugar-phosphate.…”
Section: Three-dimensional Structural Database Searchmentioning
confidence: 99%